Gerakan Perilaku Hidup Bersih dan Sehat (PHBS) dan Filantropi Bansos Mahasiswa dalam Meminimalisasi Dampak Covid-19 - ach yasin; Moch Khoirul Anwar; Hujjatullah Fazlurrahman (Jurnal Abdi Masyarakat (JAM), 2021)
The Covid -19 pandemic disaster made many students choose to stay in Surabaya, East Java. Students need to eat and drink to carry on their lives and to fulfill these needs, students will have activities outside the home. Surabaya category which is in the red zone, the possibility of contracting the virus is very high. It is unfortunate if there are students who have contracted Covid-19 because they left their rented or boarding houses to shop to meet their daily needs. Therefore, it is necessary to have a PHBS Movement in activities outside the home to prevent the transmission of covid-19. The PHBS movement includes how to wash hands using soap and running water, use masks and social distancing. Activities are carried out in the form of seminars and socialization using social media. Another activity is the distribution of aid as a form of philanthropy to students affected by Covid-19. The results of the PKM implementation are expected to be able to prevent and minimize the spread of Covid - 19 among students.